LINC00467 promotes cell proliferation and stemness in lung adenocarcinoma by sponging miR‐4779 and miR‐7978. Issue 8 (3rd November 2019) - Chang, Yanxiang; Yang, Lisheng
Abstract: Lung adenocarcinoma (LAD), as one of the most common types of lung tumors, is lethal and malignant. Long noncoding RNAs (lncRNAs) play important roles in various cancers according to many previous studies. LINC00467 was proposed to be a tumor promoter. Despite the validated promotive effect of LINC00467 on neuroblastoma progression, its regulatory mechanism in LAD remains unclear. In this study, LINC00467 expressed higher in LAD tissues and cell lines, and increased LINC00467 indicated a poor prognosis. Knockdown of LINC00467 inhibited cell proliferation, the expressions of tumor stem cell‐related genes, and cell spheroid formation ability, while it promoted cell apoptosis. miR‐4779 and miR‐7978 were reported to play antitumor roles in several cancers before. LINC00467 could combine with miR‐4779 and miR‐7978, and negatively regulated miR‐4779 and miR‐7978. miR‐4779 and miR‐7978 inhibitor could partly rescue the LINC00467 knockdown‐induced influence on cell proliferation, apoptosis, and stemness. In a word, this study innovatively investigated the mechanism of LINC00467 in LAD and verified LINC00467 exerted its carcinogenesis function by sponging miR‐4779 and miR‐7978, which may become a catalyst for generating new therapeutic targets for LAD treatment. Abstract : LINC00467 is upregulated and related to poor prognosis in lung adenocarcinoma (LAD). Knockdown of LINC00467 inhibits proliferation, promoted apoptosis, and inhibited stemness of LAD cells.